2013
DOI: 10.2174/1566524011313030013
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of DLX2 Confers a Poor Prognosis in Glioblastoma Patients by Inducing a Proliferative Phenotype

Abstract: The human Distal-less Homeobox (DLX) gene family encodes homeobox transcription factors involved in the control of morphogenesis and tissue homeostasis, which is primarily expressed in embryonic development. Recently, DLX gene family was reported to have essential roles in carcinogenesis. We have profiled whole genome expressed genes in 83 glioblastoma multiforme (GBM) patients from the Chinese Glioma Genome Atlas (CGGA) Group. Two major groups of samples were identified in mRNA expression profiles (referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The distal-free homeobox (DLX) gene family has been supported to be involved in a lot of physiological and pathological events [34]. Among them, DLX2 plays a crucial role in the development of many human cancers, including glioma and gastric adenocarcinoma cancers [35,36]. A previous study showed that DLX2 promoted the proliferation of HCC cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…The distal-free homeobox (DLX) gene family has been supported to be involved in a lot of physiological and pathological events [34]. Among them, DLX2 plays a crucial role in the development of many human cancers, including glioma and gastric adenocarcinoma cancers [35,36]. A previous study showed that DLX2 promoted the proliferation of HCC cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…DLX2 has been reported to be involved in embryonic brain, retina, and craniofacial development (de Melo et al 2005(de Melo et al , 2008Petryniak et al 2007;Gordon et al 2010). In addition to its role in development, high DLX2 expression has been found in a variety of cancers (Yilmaz et al 2011), and studies have shown that DLX2 expression associates with poor prognosis in glioblastoma and gastric cancer (Tang et al 2013;Yan et al 2013). A recent study found that DLX2 is involved in regulating TGF-β-induced growth arrest, and loss of DLX2 inhibits melanoma tumor growth and metastasis in mouse models (Yilmaz et al 2011).…”
Section: Homeobox Transcription Factor Dlx2 Identified From the Screenmentioning
confidence: 99%
“…DLX2 is a member of the DLX family that reportedly participates in tumour progression. DLX2 is a marker of poor prognosis in patients with glioma and its overexpression increases Cyclin D1 expression and cell proliferation (Yan et al, 2013). Increased DLX2 expression may correlate with advanced stage in patients with gastric adenocarcinoma and contribute to tumour development (Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%